PENANGANAN SEKOLAH DALAM MENGHADAPI KEKERASAN DI SEKOLAH (SCHOOL BULLYING) PADA PESERTA DIDIK DI SMPN 45 SURABAYA - Fajriah, Sekar; Setyowati, Raden Roro Nanik (Kajian Moral dan Kewarganegaraan, 2024)
Violence is something that can harm someone. Violence is done to hurt weaker people. Violence that occurs in schools is often a problem that must be faced by the school. The handling of the school can reduce violent behavior in students. This study aims to determine the form of violence that occurs in SMP Negeri 45 Surabaya and describe the handling given to students involved in violence at school. School handling as a process, the method used by schools in handling cases of violence that occur in schools carried out by the school with parties involved in violence whereas, violence is unlawful behavior that can cause harm to others, and cause suffering both physically, psychologically to someone. The research informants were the principal, BK teachers, and homeroom teachers at the school. This study uses qualitative descriptive research. Data is collected through the interview process, and documentation. The data is then analyzed using data analysis techniques by Miles Huberman which include data reduction, data presentation and conclusions. The results of this study show that (1) The form of violence in SMP Negeri 45 Surabaya is verbal and physical violence. (2) Handling provided through reports received and then with actions taken, namely mediation (calling victims and perpetrators) to hear problems from their respective perspectives, coaching carried out by homeroom teachers or BK teachers by providing advice and helping to straighten out accompanied by parents, and supervision is carried out to see how the perpetrator's behavior changes in the classroom after being handled so that it does not lead to behavior repeated violence